A compact class-AB bulk-driven quasi-floating gate current mirror for low voltage applications - Suadet, Apirak; Kasemsuwan, Varakorn (My University, 2013)
A compact class-AB bulk-driven quasi-floating gate current mirror is proposed. The circuit is based on an active class-A current mirror using bulk-driven quasi-floating gate (BD-QFG) MOS transistors and low voltage bulk-input pseudo-differential amplifier. The circuit can operate from a supply voltage as low as VT+VDSAT. The performance of the circuit is verified by SPECTRE, using a standard 0.18 μm CMOS process with a 0.5 V supply voltage. The circuit demonstrates low input impedance (934 Ω) and relatively high output impedance (1.13 MΩ). The circuit can drive the output current 8 times larger than the quiescent current. The power dissipation under quiescent condition is 8.2 μW. © 2013 IEEE.
Keywords: bulk-driven; class-AB; current mirror; low-voltage; quasi floating gate